Does Influencer–Follower Relationship Matter? Exploring How Relationship Norms and Influencer–Product Congruence Affect Advertising Effectiveness across Product Categories. Issue 2 (4th May 2022) - Ju, Ilyoung; Lou, Chen
Abstract: This study examines how influencer–product congruence and relationship norms (i.e., exchange versus communal) between an influencer and followers affect consumer responses to influencer-sponsored ads. In Study 1, in a low-involvement product condition (sunscreen), we found that relationship norms moderate the effect of influencer–product congruence on source credibility and brand attitudes. In particular, if the influencer–follower relationship is perceived as exchange oriented, participants in an influencer–product-congruent condition perceive higher credibility of the influencer and thus indicate more favorable brand attitudes toward the influencer-sponsored ad than those in a noncongruence condition. However, if the relationship is communal oriented, influencer–product congruence does not significantly affect participants' responses. Source credibility mediates the interaction effect between congruence and relationship norms on brand attitudes. In Study 2, we further examined how product involvement interacts with influencer–product congruence, as well as relationship norms. We found a significant three-way interaction effect among the three constructs, such that the significant moderating effect of relationship norms on influencer–product congruence is evident in a low-product-involvement condition but not in a high-product-involvement condition.